Mechanisms of Neuronal Silencing After Cortical Spreading Depression. (5th January 2016) - Sawant-Pokam, P. M.; Suryavanshi, P.; Mendez, J. M.; Dudek, F. E.; Brennan, K. C.
Abstract: Cortical spreading depression (CSD) is associated with migraine, stroke, and traumatic brain injury, but its mechanisms remain poorly understood. One of the major features of CSD is an hour-long silencing of neuronal activity. Though this silencing has clear ramifications for CSD-associated disease, it has not been fully explained. We used in vivo whole-cell recordings to examine the effects of CSD on layer 2/3 pyramidal neurons in mouse somatosensory cortex and used in vitro recordings to examine their mechanism. We found that CSD caused a reduction in spontaneous synaptic activity and action potential (AP) firing that lasted over an hour. Both pre- and postsynaptic mechanisms contributed to this silencing. Reductions in frequency of postsynaptic potentials were due to a reduction in presynaptic transmitter release probability as well as reduced AP activity. Decreases in postsynaptic potential amplitude were due to an inhibitory shift in the ratio of excitatory and inhibitory postsynaptic currents. This inhibitory shift in turn contributed to the reduced frequency of APs. Thus, distinct but complementary mechanisms generate the long neuronal silence that follows CSD. These cellular changes could contribute to wider network dysfunction in CSD-associated disease, while the pre- and postsynaptic mechanisms offer separate targets for therapy.